Explaining the effect of the level for some vital Indicators in people with DM2 and comparing them with healthy people (Eurasian Scientific Herald, 2025)
The work of collecting samples began from 11/13/2024 from Shirqat General Hospital, Salah al-Din Governorate until 2/14/2025, The study included collecting (50) samples from the people of Sharqat city, and these samples included (40) samples of people with type 2 diabetes and (10) samples of individual person who were considered as a healthy people. The study showed through the results that there is a significant increase (P≤0.05) in the level of urea concentration (45.7±6.2) mg/dl In patients with DM2 when compared with healthy individuals (29.7±4.1). The study showed through the results that there is a significant (P≤0.05) increase of creatinine concentration level (0.95±0.21) mg/dl in the in patients with DM2 when compared with healthy individuals (0.27±0.33). There were no differences significantly (P≤0.05) in the level of total protein concentration (8.2±1.34) g/dl in people with DM2 when compared with healthy individuals (7.3±0.97)